Upskilling: Do employers demand greater skill when skilled workers are plentiful? - Alicia Sasser Modestino; Daniel Shoag; Joshua Ballance (Federal Reserve Bank of Boston, 2014)
Using a large database of online job postings, we demonstrate that employee skill requirements rise when there is a larger supply of relevant job seekers. We identify this effect using variation across time, occupations, and places, which allows us to control for potentially confounding factors. We further exploit the natural experiment arising from troop withdrawals from Iraq and Afghanistan over this period as a shock to local, occupation-specific labor supply. Our estimates imply that the increase in national unemployment rates from 2007 to 2010 increased requirements for a bachelor's degree within occupations by 2.2 percentage points and increased the fraction requiring two or more years of experience by 3.5 percentage points.
Keywords: J23; J24; J63; 330; upskilling; middle skills; vacancies; labor demand; employer search